Effects of Chronic ACTH Excess on Human Adrenal Cortex - Bertagna, Xavier (Frontiers in Endocrinology, 2017)
Chronic ACTH excess leads to chronic cortisol excess, without escape phenomenon, resulting in Cushing’s syndrome. Excess adrenal androgens also occur: In females they will overcompensate the gonadotrophic loss, inducing high testosterone; in males, they will not compensate it inducing low testosterone. Chronic ACTH excess leads to chronic adrenal mineralocorticoid excess and low aldosterone levels: after an acute rise, aldosterone plasma levels resume low values after a few days when ACTH is prolonged. Two other mineralocorticoids in man, cortisol and 11 deoxycorticosterone, at the zona fasciculata, will not escape the long-term effect of chronic ACTH excess and their secretion rates will remain elevated in parallel. Over all, the concomitant rise in cortisol and 11 deoxycorticosterone will more than compensate the loss of aldosterone, and eventually create a state of chronic mineralocorticoid excess, best evidenced by the accompanying suppression of the renin plasma levels, a further contribution to the suppression of aldosterone secretion. Prolonged in vivo stimulation with ACTH leads to an increase in total adrenal protein and RNA synthesis. Cell proliferation is indicated by an increase in total DNA the resulting adrenocortical hyperplasia participates in the amplified response of the chronically stimulated gland, and the weight of each gland can be greatly increased. The growth-stimulatory effect of ACTH in vivo most likely proceeds through the activation of a local and complex network of autocrine growth factors and their own receptors; a number of compounds, including non-ACTH POMC-peptides such as γ3-MSH, have been shown to exert some adrenocortical growth effect.